Telemedicine in the Satellite Dialysis Unit: Is It Feasible and Safe? - Haroon, Sabrina; Lau, Titus; Tan, Gan Liang; Davenport, Andrew (Frontiers in Medicine, 2021)
Telemedicine has gained popularity during the recent infectious crisis. Regular and timely physician review is an essential component of care for the maintenance of hemodialysis patients. While it is widely acknowledged that telemedicine cannot fully replace the role of physical review in this group of patients with organ failure, it can perhaps reduce the reliance on physical review or serve as a filter and triage in determining which patient requires actual physical review. The use of technology in any healthcare setting should always align with existing clinical workflow and protocols. We discuss the safety and quality aspects of this new concept applied to the satellite dialysis unit.